Laboratory assays to test Cordyceps (=Isaria) fumosorosea, spirotetramat, flupyradifurone and imidacloprid against the parasitoid Encarsia guadeloupae and predator Apertochrysa astur - Rakshith, H. S.; Hegde, Jayalaxmi Narayan; Sumalatha, B. V.; Selvaraj, K.; Rajashekharappa, K.; Ganesha Naik, R.; Thippesha, D. (Biocontrol science and technology, 2025)
The lethal and sub-lethal doses of several novel insecticides, spirotetramat 15.31 OD, flupyradifurone 17.09 SL, and the entomopathogenic fungus Cordyceps fumosorosea strain ICAR-NBAIR Pfu-5, were evaluated on the parasitoid Encarsia guadeloupae and predator Apertochrysa astur. C. fumosorosea at 5 ml/L; spirotetramat 15.31 OD at 1.20 ml/L; C. fumosorosea at 2.5 ml/L + spirotetramat 15.31 OD at 1.20 ml/L were determined to be safer for immature stages and adults of E. guadeloupae and were classified as class I insecticide (harmless). C. fumosorosea at 2.5 ml/L + flupyradifurone 17.09 SL at 1.25 ml/L and flupyradifurone 17.09 SL at 2.5 ml/L were found to be slightly harmful (Class II insecticide) to adult stages of E. guadeloupae. C. fumosorosea at 5 ml/L; spirotetramat 15.31 OD at 1.20 ml/L; C. fumosorosea at 2.5 ml/L + spirotetramat 15.31 OD at 1.20 ml/L and C. fumosorosea at 2.5 ml/L + flupyradifurone 17.09 SL at 1.25 ml/L demonstrated minimal effect on larvae and adults of A. astur and were classified as class I insecticide. In contrast, with the exception of C. fumosorosea at 5 ml/L, all other test insecticides, either individually or in combination, were found to be unsafe for A. astur eggs. Imidacloprid 17.8 SL exhibited slightly harmful effects on larval stages and moderately harmful effects on adult stages of these biocontrol agents and was classified as class II and III insecticide, respectively. This study contributes new tools for use in IPM for the control of rugose spiraling whitefly, in which chemical and biological control strategies are employed concurrently.